Association of short sleep duration and short time in bed with depression: A Japanese general population survey. Issue 2 (11th December 2014) - Furihata, Ryuji; Uchiyama, Makoto; Suzuki, Masahiro; Konno, Chisato; Konno, Michiko; Takahashi, Sakae; Kaneita, Yoshitaka; Ohida, Takashi; Akahoshi, Toshiki; Hashimoto, Shu; Akashiba, Tsuneto
Abstract: Recent epidemiological studies have documented that depression is associated with short sleep duration, which may be interpreted as a consequence of comorbid insomnia and/or that of curtailment of time in bed (TIB). However, none of the studies examined association between depression and TIB. Here, we study TIB, short sleep duration and depression in the Japanese general adult population. Cross‐sectional surveys with a face‐to‐face interview were conducted in 2009 as part of the Nihon University Sleep and Mental Health Epidemiology Project (NUSMEP). Data from 2532 individuals were analyzed. The Center for Epidemiologic Studies Depression Scale (CES‐D) was used to assess the prevalence of depression with a cut‐off point of 16. Sleep habits and sleep problems during the previous month, including bed time, getting up time, sleep duration, insomnia symptoms, and hypnotic medication use were evaluated. TIB was calculated from bed time and getting up time. The prevalence of depression identified with CES‐D was 6.0% in total samples, 5.1% in men and 6.7% in women. Multiple logistic regression analysis revealed that both short sleep duration (<6 h) and short TIB (<6 h) were significantly associated with CES‐D depression after adjusting for the confounding effects of sociodemographic variables, insomnia symptoms, and hypnotic medication use. We postulate that TIB, a modifiable sleep habit, may be an important target for improvement of sleep hygiene as a means of preventing depression.